Gratitude Can Help Women At-Risk for Depression Accept Their Depressive Symptoms, Which Leads to Improved Mental Health - Tomczyk, Joanna; Nezlek, John B.; Krejtz, Izabela (Frontiers in Psychology, 2022)
Introduction Gratitude is commonly known as a positive emotion, but it can also be understood as a disposition—one’s inherent quality that includes being grateful for the positive aspects of one’s life and appreciating altruistic gifts. A growing body of research suggests that having a disposition of gratitude is positively related to wellbeing and psychological adjustment. The present study examined the extent to which acceptance of illness—a measure of adjustment to a distressing condition—mediated relationships between dispositional gratitude and wellbeing among women who had elevated levels of depressive symptoms. Methods Participants were 131 women who, based on scores on the Center for Epidemiological Studies Depression scale, were at-risk for experiencing clinical depression. Thirty-five of these participants had been diagnosed as depressed at some point in their lives and 96 had not. Participants completed measures of dispositional gratitude, wellbeing, anxiety, and acceptance of illness. Results Dispositional gratitude was positively correlated with wellbeing and was negatively correlated with depression and anxiety. Dispositional gratitude was also positively correlated with acceptance of illness. Mediational analyses found that acceptance of illness mediated relationships between dispositional gratitude and wellbeing, between dispositional gratitude and anxiety, and between dispositional gratitude and depression. Moreover, such mediation varied as a function of whether women had ever been diagnosed as depressed. Acceptance of illness was related more strongly to wellbeing for women who had been diagnosed as depressed at some time in their lives than it was for women who had never been diagnosed as depressed. Conclusion Women with elevated depressive symptoms who were more grateful (compared to those who were less grateful) were more accepting of their condition, which was related to increased wellbeing and decreased feelings of depression and anxiety.